Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3126/banko.v30i2.33482
|View full text |Cite
|
Sign up to set email alerts
|

Identification and management of heart-rot fungi

Abstract: Not Available

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…ScFM is blamed to harvest green trees and controversy arose during the implementation of the program due to the high number of trees cut in comparison to passive management followed during the past; but actually it was found that ScFM helps to remove overmature, diseased, and decayed trees from the forest and helps to maintain the forest's health [18]. Heart rot can be very hard to prevent and control but can be avoided if a tree is carefully monitored over its entire lifetime [19] and the active management scheme of ScFM enhances the monitoring activities in comparison to passive management. e sustainable practice of harvesting can enhance forest's health and also maximize the benefit by reducing the overmature trees [20].…”
Section: Timber Volume Remained In the Stumpmentioning
confidence: 99%
“…ScFM is blamed to harvest green trees and controversy arose during the implementation of the program due to the high number of trees cut in comparison to passive management followed during the past; but actually it was found that ScFM helps to remove overmature, diseased, and decayed trees from the forest and helps to maintain the forest's health [18]. Heart rot can be very hard to prevent and control but can be avoided if a tree is carefully monitored over its entire lifetime [19] and the active management scheme of ScFM enhances the monitoring activities in comparison to passive management. e sustainable practice of harvesting can enhance forest's health and also maximize the benefit by reducing the overmature trees [20].…”
Section: Timber Volume Remained In the Stumpmentioning
confidence: 99%
“…Fungi deplete the tree's hemicellulose, cellulose, and, in some cases, lignin, resulting in the tree's death (Figure 6) (Tripathi and Adhikari, 2021). Symptoms: Heart rot is difficult to diagnose since it occurs internally and can go undetected for years (Jha, 2020). Mushrooms typically grow on the trunk or branch of a tree in the later stages of heart rot.…”
Section: Heart Rotmentioning
confidence: 99%
“…External mushrooms are the fruiting bodies of fungi known as "conks" or "bracket fungi." (Jha, 2020) Wood decay is caused by heart rot fungi and following describes the types of wood decay.…”
Section: Heart Rotmentioning
confidence: 99%
See 2 more Smart Citations